Reading Batavia from the Water: Canals, Ports, and Hydrocolonialism in Iksaka Banu’s Novel Rasina - Ferdiansyah, Rafi; Ayun, Kharisma Qurrota; Khasanah, Siti Uswatun (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2025)
Eighteenth-century Batavia was often imagined as the Venice of the East, a city of canals that captivated the colonial rulers. However, behind this image, water became an arena where colonialism operated in the most subtle yet brutal ways. This study offers a hydro-colonial reading using Rasina as a starting point. A qualitative approach was adopted in this study, incorporating historical and textual analyses, with a Batavia map (1740–1760) serving as a visual reference for interpreting spatial representations. The focus of this study is not on land or fortresses, but on canals, docks, and coastlines as the arteries of the city that bind commodities, bodies, and archives into a single colonial machine. Through this lens, opium and slaves appear as two extreme faces of maritime logic. Opium became a commodity whose status could be negotiated, legal or contraband, simply by manipulating port documents. On the other hand, slaves were treated as voiceless bodies, reduced to lists of ownership and administrative stamps without room for negotiation. Rasina brings this paradox to life, showing how canals and ports became arenas of struggle between the official and shadow economies. The issue of Chinese identity further sharpened the hydro-colonial landscape of Batavia. The figures of Kapitan Cina, Kong Koan, and the Boedelkamer institution illustrate the ambiguous position of the Chinese community: the backbone of the urban economy and at the same time the object of strict control by the colonial bureaucracy. Cartographic maps of Batavia (1740-1760) reveal further that canals were not merely waterways, but lines of power that united ports, government centers, ethnic areas, and Ommelanden within a single water regime. This study concludes that Batavia was not a beautiful Venice of the East, but rather a hydro-colonial laboratory: a space where water, archives, and violence converged, forming a complex landscape of power while leaving behind a long trail of cultural scars.